Vegetation patterns and dynamics of Renosterveld at Agter-Groeneberg Conservancy, Western Cape, South Africa - Walton, Benjamin Alan (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MSc (Conservation Ecology and Entomology)--University of Stellenbosch, 2006.